Novija historiografija o grkokatoličkoj Marčanskoj (Svidničkoj/Platejskoj) biskupiji i crkvenoj uniji u Hrvatskoj - Kudelić, Zlatko (2020)
Autor analizira noviju domaću i inozemnu historiografiju o Marčanskoj (Svidničkoj/Platejskoj) biskupiji i crkvenoj uniji na području Hrvatsko-slavonske vojne krajine. Ukazuje na razlike u interpretacijama kod pojedinih autora i na moguće izvore njihovih zaključaka.
The author analyses Croatian and international historiography on the Greek Catholic diocese of Marčanska (Svidnička or Platejska) since the early 1990s, emphasizing that the increased interest in this topic at that time was partly driven by the political changes in Croatia and its surroundings. The topic has been in the focus of interest of historians dealing with the Military Frontier (Krajina) and the Catholic Church as well as authors of the syntheses of the history of Croatia and the Serbian Orthodox Church in Croatia. A number of scholars in Croatia have accepted J. Šimrak’s conclusions about the success of the union in the early 17th century as a consequence of the wider Union movement and the responsibility of the Vienna court and some Zagreb bishops for its failure. On the other hand, foreign historians have accepted conclusions about the Habsburg religious policy from Austrian historiography written in the second half of the 19th and the early 20th century, repeating stereotypes and inaccurate data that were not scientifically evaluated, such as the hypothesis about the Jesuits as the main factors in the expansion of the union and the constant Catholic pressure on the population of the Orthodox frontier region, allegedly carried out by the Krajina commanders. Only a few historians have indicated the unsustainability of these hypotheses and pointed out that the Frontier was a desirable settlement area for Orthodox Christians from the Ottoman Empire. There are noticeable differences among the scholars as to the interpretation of the beginnings, motives, and reach of the union, as well as different understandings of the basic concepts concerning this issue, and due to the lack of relevant studies and the use of unreliable older historiography, these 18th-century events have been described very scantily and inaccurately, especially the reign of Charles VI.
Bibliografske bilješke uz tekst ; bibliografija i izvori: str. 194-200.
Sažetak ; Summary.
Keywords: Historiografija -- Crkvena unija -- Pravoslavlje -- Vlasi; Marčanska biskupija -- Zagrebačka biskupija -- Pećka patrijaršija; Vojna krajina